1990
DOI: 10.1177/070674379003500304
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Adjustment and Quality of Life following Heart Transplantation

Abstract: This article describes the pre-operative psychosocial and quality-of-life adjustment of a consecutive series of 27 heart transplant recipients and the adjustment of the 24 survivors at 12 months follow-up. Pre-operatively, 14 had a psychiatric diagnosis and this figure had dropped to five at 12 months follow-up. Those patients without a psychiatric diagnosis preoperatively had not developed one at follow-up. There was a significant correlation between pre-operative psychiatric diagnosis and a rating of poor me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(20 citation statements)
references
References 3 publications
2
16
1
1
Order By: Relevance
“…[21][22][23][24][25] With overall functional disabilities and symptom distress improving after transplant, patients are generally more satisfied with life after transplant, as we also found in our study. 26,27 However, after heart transplantation, work-related disability continues to be the greatest disability, as noted in a previous report from our research.…”
Section: Discussionsupporting
confidence: 82%
“…[21][22][23][24][25] With overall functional disabilities and symptom distress improving after transplant, patients are generally more satisfied with life after transplant, as we also found in our study. 26,27 However, after heart transplantation, work-related disability continues to be the greatest disability, as noted in a previous report from our research.…”
Section: Discussionsupporting
confidence: 82%
“…For example, Strauss et al (1992) found "no specifically high incidence of psychopathology. " Mai, McKenzie, and Kostuk (1990) found that, overall, the transplant patients (N ϭ 24) displayed substantial improvement in psychosocial adjustment and quality of Organ Transplant Experience life in the 12 months following transplant. Fourteen of those Ss had a psychiatric diagnosis pretransplant, and only 5 had such a diagnosis at one year posttransplant.…”
Section: Range Of Findingsmentioning
confidence: 97%
“…7,32,33 Nevertheless, depression in cardiovascular patients is a well-known risk factor for future mortality and morbidity. 17 Studies investigating the depression rates after heart transplantation are difficult to interpret and reconcile owing to different reasons: lack of adjustment for the length of the period between transplant and psychiatric assessment; small samples available for psychiatric diagnostic studies 34 ; and diagnostic decisions not based on clinical interview schedules. 34 This work selected a large sample of patients undergoing heart transplantation at the same center (n ϭ 137) and assessed them Ͼ10 years after surgery with an internationally validated psychometric survey.…”
Section: Mortality and Overall Quality Of Life In The Long Term Aftermentioning
confidence: 99%